Nicotine-Induced Oxidative Stress in Human Primary Endometrial Cells. (May 2019) - Khademi, Fatemeh; Totonchi, Hamidreza; Mohammadi, Neda; Zare, Razieh; Zal, Fatemeh
Nicotine is a major component of tobacco plants and is responsible for the development of reproductive problems in smokers. Nicotine has been recognized to result in oxidative stress by inducing the generation of reactive oxygen species (ROS) in some parts of female reproductive system, but the effect of nicotine on endometrium that plays an important role in reproductive biology stays unexplored. The aim of this work was to clarify the direct effects of nicotine administration on the antioxidant defense system and lipid peroxidation in human endometrial cells. Human endometrial stromal primary cells were treated with nicotine (0, 10 −11, 10 −8, and 10 −6 M) for 24 hours. On nicotine administration, the endometrial cells were associated with a decrease in antioxidant defense markers such as Glutathione (GSH) level, glutathione peroxidase (GPx), glutathione reductase (GR), and catalase (CAT) enzymes activity and higher levels of malondialdehyde (MDA) in a dose-dependent manner when compared to the control. We concluded that nicotine as a pro-oxidant affects the oxidative state of the endometrial cells.